2014
DOI: 10.1016/j.jdeveco.2014.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Addressing antibiotic abuse in China: An experimental audit study

Abstract: China has high rates of antibiotic abuse and antibiotic resistance but the causes are still a matter for debate. Strong physician financial incentives to prescribe are likely to be an important cause. However, patient demand (or physician beliefs about patient demand) is often cited and may also play a role. We use an audit study to examine the effect of removing financial incentives, and to try to separate out the effects of patient demand. We implement a number of different experimental treatments designed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
127
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(132 citation statements)
references
References 51 publications
2
127
3
Order By: Relevance
“…A review of antibiotic use in China demonstrated that 80% of inpatients and 50.3% of outpatients were prescribed with antibiotics, and as many as 75% of patients with seasonal influenza were treated with antibiotics [11]. With one-fifth of the world’s population living in China, this is a serious global concern.…”
Section: Introductionmentioning
confidence: 99%
“…A review of antibiotic use in China demonstrated that 80% of inpatients and 50.3% of outpatients were prescribed with antibiotics, and as many as 75% of patients with seasonal influenza were treated with antibiotics [11]. With one-fifth of the world’s population living in China, this is a serious global concern.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] The average number of prescriptions per encounter at township health centers has been reported to be 43-150 percent more than the standard recommended by the World Health Organization for outpatients in developing countries and could contribute to antibiotic resistance. 13,14 Moreover, insurance rates have risen over the past decade, 15 and people with insurance are more likely than others to receive inappropriate prescriptions. 16 To address these problems, in April 2009 China introduced its national essential drug list, with the goal of promoting the availability, safety, and appropriate use of essential drugs while reducing excessive household spending on clinically unnecessary medicines.…”
mentioning
confidence: 99%
“…Types of responsible pathogens are complicated and in most of the case is mainly Gram negative bacterium. Incidences of complex infection have gradually increased day by day because of antibiotics abuse (Hur et al, 2012;Chidambaram, 2014;Currie et al, 2014). So, to overcome these difficulties, we have to treat them from all kinds of aspects by analyzing.…”
Section: Discussionmentioning
confidence: 99%